Argumentación, Comprensión y Polifonía. Reflexiones desde el aula de clase universitaria (2015)
This article considers a problem affecting teaching and learning communicative and argumentative skills in the university academic space, in order to suggest some ideas for future developments. The question that guides this reflection is: How to address the demand for understanding by undergraduates in oral and written elocution? To solve this question, it will be done the approach of three issues: (a) the contribution of a dialectical approach of argumentation, (b) the hermeneutical characteristics of understanding and (c) the importance of the phenomena of polyphony of language in the construction of meaning.